Transforming Non-Renewable Resource Economies (NREs) - Battaile, Bill (IMF Working Papers; Working Paper ;, 2015)
This paper provides an empirical benchmarking of growth, productivity and export patterns for developing NREs against other low and middle income developing countries, to inform policy discussions and future analytical work. There is stark heterogeneity in the association of resource sector and overall growth outcomes, by commodity and degree of dependence. Over the long term, inter-sectoral growth dynamics have been more muted for NREs than other developing countries, especially at lower incomes. Despite productivity convergence in mining, as expected, productivity growth in manufacturing and services was generally lower in NREs. Exceptions are few, in East Asia and the CIS area which experienced broad-based productivity growth. NRE product exports are more concentrated and relatively less complex, though we find increasingly diversified service export baskets. Technological progress and specialization in trade in services may offer diversification options for the future.